Integrative Approaches: A Paradigmative and Implementative Review in PAI Learning - Nuratika; Haris Riadi; Sari Haryati (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
The integrative approach in Islamic Religious Education (PAI) Learning is a paradigmatic response to the challenges of disintegration of knowledge, educational dualism, and the reduction of spirituality that are still emerging in modern educational practices. This research aims to comprehensively examine the philosophical, conceptual, and implementive foundations of the integrative approach in PAI learning, as well as formulate operational models that are relevant to the needs of 21st century learning. This research uses a literature method with themetical-critical analysis of various classical and contemporary Islamic literature, national education policies, and empirical research related to the integration of knowledge. The results of the study show that the integrative paradigm rests on the epistemology of monotheism which views religious science and general science as a complementary unit, not a dichotom. The implementation of an integrative approach in PAI learning results in three main forms: concept integration, value integration, and pedagogical action integration. All three have been proven to increase the relevance of learning, depth of understanding, and internalization of Islamic values through contextual and holistic learning. This study concludes that an integrative approach is not just a methodological choice, but a strategic need to build an adaptive, moderate, and spiritual character strengthening Islamic education ecosystem.